Analysis of The Effect of Facility and Service Quality on Consumer Satisfaction - Erwin Pratama Sinaga; Marlina Siregar; Nurintan Asyiah Siregar (Quantitative Economics and Management Studies, 2022)
This study aims to determine the variable of facilities (X1 ) and service quality (X2 ) and the variable of customer satisfaction (Y). In this study, the population used was all consumers who had visited the Hotel Platinum Rantauprapat at least 1 time, and the sample was taken using the unknown population formula for as many as 100 respondents. Data was collected by distributing questionnaires using google Forms and measured by a Likert scale. The data analysis technique in this study uses PLS (partial least square) analysis which is a variant-based Structural Equation Modeling (SEM) equation analysis using SmartPLS 3 software. The results of this study indicate that facilities and service quality have a positive and significant effect on customer satisfaction